Model predictive control of six-phase induction motor drives using virtual voltage vectors - González Prieto, Ignacio; Durán-Martínez, Mario Javier; Aciego Gallardo, Juan José; Martín, Cristina; Barrero, Federico (IEEE, 2017)
The most serious and recent competitor to the standard field oriented control for induction motors (IM) is the finite control set model predictive control (FCS-MPC). Nevertheless, the extension to multiphase drives faces the impossibility to simultaneously regulate the flux/torque and the secondary current components (typically termed x − y in the literature). The application of a single switching state during the whole sampling period inevitably implies the appearance of x − y voltage/currents that increase the system losses and deteriorate the power quality. These circulating currents become intolerably high as per the unit x − y impedance and the switching frequency diminish. Aiming to overcome this limitation, this work suggests the integration of virtual voltage vectors (VVs) into the FCS-MPC structure. The VVs ensure null x − y voltages on average during the sampling period and the MPC approach selects the most suitable VV to fulfill the flux/torque requirements. The experimental results for a six-phase case study compare the standard FCS-MPC with the suggested method, confirming that the VV-based MPC maintains the flux/torque regulation and successfully improves the power quality and efficiency.
Keywords: Motores de inducción; Ingeniería eléctrica; Induction motors (IM); Model predictive control (MPC); Six-phase drives; Virtual voltage vectors (VVs).